Control of Escherichia coli O157:H7 and Listeria monocytogenes in meat and poultry products with chemicals and heating treatments - Shen, Cangliang, author; Sofos, John, advisor; Kendall, Patricia, committee member; Belk, Keith, committee member; Scanga, John A., committee member (Colorado State University. Libraries, 2010)
Objectives of studies included in this dissertation were to evaluate the effects of chemical antimicrobials, such as cetylpyridinium chloride, lactic acid, hops beta acids, commercial salad dressings, and heat treatments including cooking with various appliances and microwave oven heating to control Escherichia coli 0157:H7 in moisture enhanced noninact beef and Listeria monocytogenes on ready-to-eat (RTE) meat and poultry products. In the first study, the effect of different cooking appliances on thermal inactivation of E. coli 0157:H7 in nonintact beef steaks of different thickness was evaluated. In general, the thicker the steaks, the higher the reduction levels reached, and roasting in a standard kitchen oven showed the best inactivation effect compared to the other cooking appliances. The second study evaluated thermal inactivation of E. coli 0157:H7 in nonintact beef steaks with pan-broiling or roasting appliances set at different temperatures. Results showed that setting the cooking appliances at higher temperatures resulted in higher reduction levels of E. coli 0157:H7 cells in nonintact beef steaks compared to the lower ones. The third study involved comparison of inactivation of different types of stress-adapted or unstressed E. coli 0157:H7 cells, inoculated in moisture enhanced nonintact beef steaks with various brining solutions and cooked by pan-broiling on an electric skillet. It was evident that acid stress-adapted cells were more resistant to heat treatment, while cold or desiccation stress-adapted cells were more Hi sensitive to heat treatment than controls. The lowest pathogen counts survived during cooking of beef steaks moisture enhanced to include cetylpyridinium chloride or lactic acid for all stressed inocula tested, thus, indicating that cetylpyridinium chloride and lactic acid could be considered as potential antimicrobial agents for use in beef brining solutions. An additional study evaluated the antilisterial activity of hops beta acids (HBA) in broth medium. HBA exhibited promising antilisterial activity in culture broth, and its activity was increased with increasing concentrations (0.5 to 5.0 pg/ml), and when combined with potassium lactate (1%), sodium diacetate (0.25%), or acetic acid (0.1%), at 4°C. In a subsequent study, HBA applied as dipping solutions (0.03 to 0.10%) on frankfurters, inoculated with L. monosytogenes, vacuum packaged and stored at 4 or 10°C, inhibited pathogen growth for 30 to 50 (4°C) or 20 to 28 days (10°C). The last two studies were designed to detect the antilisterial effects of commercial salad dressings, oil with vinegar or lemon juice, on artificially inoculated frankfurters, diced ham and turkey breast during simulated home storage, without or with prior microwave heating for 30 s or 45 s. Results indicated that microwave heating followed by immersing in salad dressings, especially oil with vinegar, could potentially contribute to control of L monocytogenes on RTE meat and poultry products in the home environment. The results of all studies in this dissertation indicated that certain chemical antimicrobials and heating treatments could be effectively to control E. coli 0157:H7 and L. monocytogenes in meat and poultry products.
Covers not scanned.
Keywords: Foodborne diseases -- Prevention; Anti-infective agents; Escherichia coli O157:H7; Listeria monocytogenes